Dizziness in an avid cyclist: an unusual presentation of a common problem. Issue 12 (6th December 2021) - Sinha, Aish; Demir, Ozan M; Ellis, Howard; Perera, Divaka
Abstract: Background: Presyncope and syncope are common presentations with a wide range of differential diagnoses; when it occurs primarily on exertion, a cardiovascular cause is more likely. Structural abnormalities and primary rhythm disturbances are the usual culprits in these patients. Case summary: A 75-year-old gentleman presented with a history of progressive exertional presyncope. His investigations demonstrated normal cardiac structure, function, and rhythm. He underwent an exercise stress test, which demonstrated a significant reduction in peak blood pressure with equivocal electrocardiogram changes and absence of ischaemic symptoms. In view of his age and gender, a computerized tomography coronary angiogram (CTCA) was organized to exclude obstructive coronary artery disease (CAD). Intriguingly, the CTCA demonstrated a severe proximal left anterior descending (LAD) artery stenosis. This stenosis was confirmed to be functionally significant using invasive coronary physiology and was treated with percutaneous coronary intervention. At follow-up, there was no recurrence of exertional presyncope and the patient was continuing to return to his baseline function. Conclusion: Presyncope and/or syncope as the sole manifestation of obstructive CAD, in the presence of normal ventricular function and valves, has rarely been reported. Myocardial ischaemia-mediated presyncope and/or syncope may be secondary to numerous mechanisms, which are described in this case report. Revascularization of the functionally significant proximal LAD stenosis resulted in cessation of exertional presyncope in our patient. The long-term outcome of revascularization in patients with presyncope and syncope needs to be further investigated.